Pengaruh Pengetahuan Investasi dan Literasi Keuangan terhadap Keputusan Berinvestasi Mahasiswa Politeknik Negeri Sriwijaya di Pasar Modal - Judika Larisma Sitinjak; Afrizawati Afrizawati; Sari Lestari Zainal Ridho (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
The existence of this study aims to determine the effect of investment knowledge and financial literacy simultaneously and partially on the investment decision of Sriwijaya State Polytechnic students in the capital market. The data analysis used in this research is multiple linear regression analysis. The results of the partial analysis (T test): 1. the investment knowledge variable (X1) has a significant effect on the investment decisions of Sriwijaya State Polytechnic students in the capital market 2. The financial literacy variable (X2) has a significant effect on the investment decisions of Sriwijaya State Polytechnic students in the capital market. The results of this study also indicate that the investment knowledge variable has a dominant effect on the investment decision of Sriwijaya State Polytechnic students in the capital market.